Green Energy towards Sustainability from the Islamic Perspective - Abdul Jabar, Nur Hidayah; Ilham, Zul; Saifuddeen, Shaikh Mohd; Rahman, Noor Naemah Abdul (SustaiN Society in Kyoto, Japan, 2015)
Sustainable development is a concept mooted to ensure that the needs of the present are met without compromising the needs of the future. Islam has outlined a number of concepts for ensuring that the environment is managed in a responsible and sustainable manner. These concepts are wisdom (hikmah), justice (‘adl), public interest (maslahah) and innovation (ijtihad). The framework of higher purposes of Islamic Divine law or maqasid al-shariah also provides guidance by highlighting five objectives (viz. faith, life, intellect, progeny and property) that need to be protected in carrying out development. However, the challenge lies in putting these concepts and approaches into practice. While there is a good theoretical understanding of these Islamic concepts and approaches, the reality is that many still do not practice what they know in their individual daily lives as well as in policy formulation. Environmental issues including green energy production should not be dismissed simply as a worldly affair. As such, it is imperative for Muslims to not only be aware of these issues, but also to put sustainability into practice in order to achieve the “good life” concept or hayattayibbah.